Left behind II Tribulation Force - Tabarrok, Nicholas D.; Patus, John.; Lalonde, Paul, 1961-; Corcoran, Bill.; Cameron, Kirk, 1970-; Johnson, Brad, 1959-2022.; Gilyard, Clarence, Jr., 1955-2022.; Stephens, Janaya, 1974-; Currie, Gordon, 1965-; Noble, Chelsea, 1964-; Bridges, Krista; Mykytiuk, Lubomir; et al. ([United States] : Cloud Ten Pictures, 2002)
A week after the Rapture, millions of people have vanished into thin air, a desperate world turns to the United Nations president. Basking in the adoration and trust of the people, he seems to have the entire planet at his command. But a small group, the Tribulation Force, is aware of his true and sinister identity. Now the group must embark on a dangerous mission to open the eyes of the world to tell the truth to anyone who will listen.
DVD, 5.1 Dolby digital.
Closed-captioned.
Kirk Cameron, Brad Johnson, Clarence Gilyard, Janaya Stephens, Gordon Currie, Chelsea Noble, Krista Bridges, Lubomir Mykytiuk.
Director of photography, Michael Storey ; editor, Michael Doherty ; music, Gary Koftinoff ; costume designer, Sharon McDonell ; production designer, Harold Thrasher.
Based on the novel by Tim F. LaHaye and Jerry B. Jenkins.
MPAA rating: Not rated.
Keywords: Steele, Rayford (Fictitious character) -- Drama; Rapture (Christian eschatology) -- Drama; Antichrist -- Drama; CHRISTIAN THRILLER; Antichrist; Rapture (Christian eschatology); Steele, Rayford (Fictitious character); DVD-Video discs; Feature films; Films for the hearing impaired; Video recordings for the hearing impaired; Drama